Hands-on Educational Labs for Cyber Defense Competition Training (Journal of The Colloquium for Information Systems Security Education, 2022)
Cyber Defense Competitions provide students with challenging, hands-on, fun, and close to real world opportunities to learn, practice, and perform tasks that they will be expected to complete as cybersecurity professionals. The current availability of training resources focused on Cyber Defense Competitions is limited. We introduce CYOTEE: CYbersecurity Oriented Training Environment and Exercises. CYOTEE provides a set of nine fully modifiable and freely available hands-on laboratory activities intended to help students gain skills needed to be successful at Cyber Defense Competitions. This article provides details for two of those hands-on labs: (1) Linux Hardening and (2) Windows Active Directory Hardening. CYOTEE lab descriptions and setup scripts may be found on the GitHub repository (https://github.com/CenterForSecureAndDependableSystems/CYOTEE).
Keywords: Cyber defense; Cyber defense competitions; Hands-on labs; Windows Active Directory hardening; Linux hardening; NICE Framework